Effect of Grinding and Regenerative Heat Treatment on the Fracture Resistance of a Zirconia/Porcelain Veneer Interface - Candido, Lucas Miguel [UNESP]; erreira, Eduardo Bellini; Pinell, Lígia Antunes Pereira [UNESP] (My University, 2022)
Purpose: To experimentally assess the effect of regenerative heat treatment (HT) on yttria-stabilized tetragonal zir conia polycrystalline ceramic (Y-TZP) to guarantee veneer adhesion strength.Materials and Methods: One surface of bar-shaped Y-TZP specimens was ground (G) with a diamond stone, while the control samples (C) were not. Groups C900 and G900 were submitted to HT at 900°C for 60 min, whereas groups C1000 and G1000 were submitted to HT at 1000°C for 30 min. The treated surfaces were characterized by x-ray diffractometry (XRD), scanning electron microscopy (SEM), and optical and mechanical profilometry. The energy release rate through interface fracture was determined by a four-point bending test on notched Y-TZP veneered specimens. XRD was refined by the Rietveld method, mean roughness (Ra) and energy release rate were submitted to two-way ANOVA ( 0.05), and the images were analyzed descriptively.Results The monoclinic phase (vol%), means of Ra (μm), and the energy release rate (J/m2) were, respectively: C 1.2/0.17/6.8, C900 0.0/0.18/6.6, C1000 = 0.0/0.18/7.6, G 2.6/1.16/8.3, G900 0.0/1.07/8.0, and G1000 = 0.0/1.01/5.7. The surface fraction of monoclinic zirconia increased by grinding and decreased by HT. Ra also increased after grinding (p 0.005) but remained unaltered after HT (p 0.22). Increased irregularity was ob served in the G groups and a subtle smoothing of the surface after HT. After the fracture of the bilayers, a residual amount of porcelain could be seen on the zirconia surface in all groups. The energy release rate was statistically equal among all groups (p 0.05).Conclusion Heat treatment after grinding completely restored the tetragonal phase of zirconia without altering the energy release rate during interfacial fracture
Keywords: Dental prosthesis; Heat treatment; Surface properties; X-ray diffraction; Zirconia